2021
DOI: 10.52206/jsmc.2021.11.1.30-33
|View full text |Cite
|
Sign up to set email alerts
|

Management Of Depressed Skull Fracture

Abstract: Background: Head injury is the most serious problem all around the world. Over the last 200 years both surgical and conservativemanagement have been evolved. Chronological surgical management yields better outcome by decreasing mortality andmorbidity. Wound debridement, repair of dural defect and closure of wound are standard principles in management.Objective: To study the outcomes of surgical management of depressed skull fracture.Material and methods: This study was conducted in Shifa Medical center from 1s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(4 reference statements)
0
0
0
Order By: Relevance
“…According to a research by Asif M. et al (16), of the 100 patients with depressed skull fractures they operated on, 55% had GCS 13 to 15. In a 7-year study of 98 instances with depressed fractures, Ali M and Ali L (22) found that 14% and 9% of the individuals had CSF leaks, 7% had extradural hemorrhages, and 15% of individuals had broad skull deformation. Clinical and radiological characteristics are also recognized as the signs of emergence following surgical elevations of depressed skull fractures.…”
Section: Discussionmentioning
confidence: 99%
“…According to a research by Asif M. et al (16), of the 100 patients with depressed skull fractures they operated on, 55% had GCS 13 to 15. In a 7-year study of 98 instances with depressed fractures, Ali M and Ali L (22) found that 14% and 9% of the individuals had CSF leaks, 7% had extradural hemorrhages, and 15% of individuals had broad skull deformation. Clinical and radiological characteristics are also recognized as the signs of emergence following surgical elevations of depressed skull fractures.…”
Section: Discussionmentioning
confidence: 99%